2021
DOI: 10.1111/csp2.553
|View full text |Cite
|
Sign up to set email alerts
|

Invasive species increase biodiversity and, therefore, services: An argument of equivocations

Abstract: Some critics of invasion biology have argued the invasion of ecosystems by nonindigenous species can create more valuable ecosystems. They consider invaded communities as more valuable because they potentially produce more ecosystem services. To establish that the introduction of nonindigenous species creates more valuable ecosystems, they defend that value is provisioned by ecosystem services. These services are derived from ecosystem productivity, the production and cycling of resources. Ecosystem productivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…As a result of invasions, grasslands may experience changes to their hydrologic regime, nutrient accumu-lation and cycling, and carbon sequestration [17]. It is widely acknowledged that the fast proliferation and worldwide dispersal of invasive species are major contributors to the degradation of biodiversity around the world [9,16]. According to [2], bioinvasion is an important aspect of global change and one of the key reasons why species become extinct.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of invasions, grasslands may experience changes to their hydrologic regime, nutrient accumu-lation and cycling, and carbon sequestration [17]. It is widely acknowledged that the fast proliferation and worldwide dispersal of invasive species are major contributors to the degradation of biodiversity around the world [9,16]. According to [2], bioinvasion is an important aspect of global change and one of the key reasons why species become extinct.…”
Section: Introductionmentioning
confidence: 99%
“…We found that alternative indicators for a single ecosystem property can conflict, as they did for the two measures of coastal marine biodiversity in our study. Additionally, even if a single indicator (such as Simpson diversity) is preferred, increases in diversity are not universally desirable (e.g., due to introductions of nonindigenous species; Lean, 2021). We found that coastal marine invertebrate family density was higher in Puget Sound at more urbanized sites when the extent of upland urbanization was small relative to paired, less urbanized sites (Figure 2; also see Ives et al, 2016).…”
Section: Discussionmentioning
confidence: 79%
“…The PVA seems to reflect the population trends of mink seen in the Danish NGBR and may therefore be reliable in estimating the extinction rate of other non-native species and for evaluation the parameters affecting the species the most [ 5 ]. Which means the PVA can be a viable tool to improve the management of invasive species, and conservation of biodiversity as the invasive species can affect the indigenous fauna community [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%